Improved coupling analysis on the coordination between socio-economy and carbon emission. (November 2018) - Shen, Liyin; Huang, Yali; Huang, Zhenhua; Lou, Yingli; Ye, Gui; Wong, Siu-Wai
Highlights: The limitation of traditional CCD model is revealed. An improved CCD model is introduced. The effectiveness of the improved model is demonstrated in 30 case provinces. The dynamic evolution and spatial distribution of coordination degree in the sample cases are analyzed. Abstract: Effective evaluation on the coordination between socio-economy (V) and carbon emission (W) is essential for sustainable urban planning, and this study introduces an improved coupling coordination degree (CCD) model for conducting such evaluation. The limitation of the traditional CCD model has been examined. The effectiveness of the improved CCD model is demonstrated with its application in 30 case provinces of China by using the data collected for the period 1995–2015. The results show that: (1) The subjectivity embodied in the traditional CCD model in analyzing the coordination between V and W significantly distorts the true coordination between the two systems. (2) The improved CCD model is effective as its application can reflect the reality of the sample cases. (3) The average coordination degrees of the 30 case provinces for the surveyed period show an upward evolution, and the coordination statuses of these provinces have been transforming from low-grade symbiosis to high-grade symbiosis. (4) The spatial distribution of coupling coordination degree in China is characterized by a higher degree of coordination in the Eastern provinces. The results of applying the improved coupling coordination degree model can help decision makers formulate effective sustainable measures to balance socio-economic development with carbon emission reduction.